Chronobiology : Biological timekeeping - Chronobiology: Biological timekeeping; Dunlap, Jay C.; Loros, Jennifer J.; DeCoursey, Patricia J. (Sunderland, Massachusetts, Sinauer Associates Inc, Publishers, 2004)
This book covers circadian rhythmicity; analyses of the behavioural and ecological importance of rhythms and their theoretical bases; the comparative anatomy, physiology, genetics and molecular biology of organisms within circadian clocks; real-world examples; classic research and 6 cutting-edge research areas.
Appendix 383-385p.; Glossary 387-390p.; Index 393-406p.
Keywords: Circadian Rhythms; Pacemaker system; Molecular biology; biological timing from unicells to humans; Zoology